1975
DOI: 10.1016/0002-9610(75)90252-4
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hemangioma

Abstract: A case is presented of a fifty-six year old man with a thyroid hemangioma presenting as a neck mass with tracheal deviation and unilateral vocal cord paralysis. A standard thyroid scan yielded equivocal findings. The diagnosis was determined preoperatively by the use of a 99m-technetium angiogram that disclosed the vascular nature of the lesion. Subsequent arteriography demonstrated the main arterial supply of the mass to be from both inferior thyroid arteries. Operative removal of the mass was accomplished th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…because hemangiomas are prone to hemorrhaging during operation; around 2000 ml of blood loss is reported in adults (10).Thus, it is important to maintain the integrity of the capsule, which can signi cantly reduce the risk of hemorrhaging and avoid a residual relapse. In our case, the nature of the mass was unclear before the operation, and its blood supply was rich.…”
Section: Discussionmentioning
confidence: 99%
“…because hemangiomas are prone to hemorrhaging during operation; around 2000 ml of blood loss is reported in adults (10).Thus, it is important to maintain the integrity of the capsule, which can signi cantly reduce the risk of hemorrhaging and avoid a residual relapse. In our case, the nature of the mass was unclear before the operation, and its blood supply was rich.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Hemangioma rarely occurs in the thyroid gland, and only 23 cases have been reported until 2005 [ 9 ] (Table 1 ). In 1975, Pickleman et al [ 10 ] were the first to report a case with thyroid hemangioma in the left lobe of thyroid gland (size 7.5 × 3.0 × 2.0 cm). Maciel et al [ 11 ] described a case with large thyroid hemangioma (size 22 × 21 × 17 cm, weight 2800 g), which was the largest one up to date.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] A lesion with larger size and the hemorrhage during the operation should not be overlooked by the surgeon, and over 2 L of blood loss had been reported in surgery. [ 10 ] Thus, sufficient preoperative preparation is very crucial to have a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hemangioma is extremely rare and there are only a few case reports in the literature 2–7. In 1975, Pickleman et al reported in the first case, the diagnosis of which was made using 99mTc angiography 8. As described in the literature, hemangiomas can harbor calcifications or phleboliths 6.…”
Section: Discussionmentioning
confidence: 99%